2012
DOI: 10.1111/j.1600-0722.2012.00983.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of surface properties of resin‐based composites on in vitro Streptococcus mutans biofilm development

Abstract: The aim of this in vitro study was to evaluate the influence of physicochemical surface properties of resin-based composites on Streptococcus mutans biofilm formation. Specimens were prepared from each of four resin-based composites by polymerization against Mylar strips. Half of the number of specimens received no further surface treatment, whereas the other half were subjected to a polishing treatment. Surface roughness (SR) and topography were assessed using profilometry and atomic force microscopy. Surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
78
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 37 publications
2
78
1
2
Order By: Relevance
“…In the present study, because the SFE of all samples was approximately 50 mN/m, we presume that SFE can be altered by bacterial adhesion at 20 mN/m. Ionescu et al reported that SFE is affected more by initial bacterial adhesion than by long-term cultivated biofilms, which is inconsistent with our results (36). This difference may be attributable to the 24 h cultivation time in our study.…”
Section: Discussioncontrasting
confidence: 57%
“…In the present study, because the SFE of all samples was approximately 50 mN/m, we presume that SFE can be altered by bacterial adhesion at 20 mN/m. Ionescu et al reported that SFE is affected more by initial bacterial adhesion than by long-term cultivated biofilms, which is inconsistent with our results (36). This difference may be attributable to the 24 h cultivation time in our study.…”
Section: Discussioncontrasting
confidence: 57%
“…25,34,43 A limitation of most of the methods used for the SFE calculation though is that the Young equation assumes that the solid surface is rigid, chemically homogemous, and smooth on an atomic scale. 39 The selection of the probe liquids was also based on the experimental protocols of relevant studies.…”
Section: Discussionmentioning
confidence: 99%
“…28 , while in ceram x one the lower bacterial adhesion may be due to the nano-ceramic filler used in its construction giving it a higher filler loading and smoother surface which yields a smoother surface with subsequent lower adhesion of bacteria, and this in agreement with the study conducted by Ionescu A who concluded that the proportions of resin matrix and filler particles on the surface of resinbased composites strongly influence S mutans biofilm formation in vitro, suggesting that minimization of resin matrix exposure might be useful to reduce biofilm formation on the surface of resinbased composites. 29 Both Z250 and Herculite classic have nearly the same tendency for bacterial adhesion also Z 250 used as indirect resin composite it was cured by the direct LED without any furnace which may yielded degree of conversion similar to that of Herculite, also they have similar filler size so under the same finishing and polishing procedure they gave nearly equal surface characters which explains the similarity in bacterial adhesion and this in accordance with Celik C et al who studied the effect of finishing and polishing procedures on surface roughness of tooth-colored materials and found that the smoothest surface was generated with Sof-Lex Pop-on disks for all the materials tested.…”
Section: Discussion:-mentioning
confidence: 99%